High-toughness samarium-cobalt magnet (blank) and preparation method thereof

By adding micron-scale copper titanate (CCTO) to samarium-cobalt magnetic powder and combining with the efficient preparation process of samarium-cobalt magnetic powder, the problem of easy cracking of samarium-cobalt magnets during processing is solved, and high toughness and good magnetic properties are achieved, reducing production costs.

CN119852046APending Publication Date: 2025-04-18CHENGDU SILVER MAGNETIC MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510119607.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing samarium-cobalt magnets are prone to cracking during processing, and the existing toughening technology is costly and has poor results, resulting in room for improvement in the mechanical and magnetic properties of the magnets.

Method used

High toughness of samarium-cobalt magnet was prepared by adding micron-scale copper calcium titanate (CCTO) to samarium-cobalt magnetic powder, mixing in a ratio of 0.1%-1.5% by weight, and oriented, pressing, cold isostatic pressing, sintering and aging treatment by rare earth permanent magnet molding press.

Benefits of technology

The high toughness and good magnetic properties of samarium-cobalt magnets are achieved, which reduces the processing cracking rate and production costs, has extremely small magnetic performance losses and significantly improved mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005258575740000071
    Figure BDA0005258575740000071
Patent Text Reader

Abstract

The invention relates to the technical field of magnet materials, in particular to a high-toughness samarium-cobalt magnet (blank) and a preparation method thereof. Wherein the samarium-cobalt magnet is prepared from samarium-cobalt magnetic powder and micron-sized copper calcium titanate; wherein the particle size of the samarium cobalt magnetic powder is 4-15 microns; the use amount of the micron-sized copper calcium titanate is 0.1 wt%-1.5 wt% of the samarium cobalt magnetic powder. According to the samarium-cobalt magnet, magnet cracking can be reduced, and the product percent of pass is ensured; and the excellent mechanical property of the magnet can be ensured, and meanwhile, the magnet can have relatively good magnetic property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnet materials, in particular to a high-toughness samarium cobalt magnet and a preparation method thereof, belonging to the rare earth permanent magnet material technology. Background Art

[0002] With the development of a new generation of aircraft engines, higher requirements are placed on high-temperature magnets with long-term operating temperatures greater than 60°C. SmCo permanent magnets with high Curie temperature, low temperature coefficient, better corrosion resistance and thermal stability have become the preferred material. However, samarium cobalt magnets have the disadvantages of high hardness and prominent brittleness, which makes samarium cobalt magnets prone to cracking during processing and have a high scrap rate. Therefore, in order to improve the machinability of samarium cobalt magnets, samarium cobalt magnets are usually toughened and modified to improve the machinability of samarium cobalt magnets and avoid the problem of a large number of magnets being scrapped due to hard and brittle defects.

[0003] At present, there are two main methods to improve the toughness of samarium cobalt magnets:

[0004] (i) By changing the process and controlling the aging process, a 2:17 type of samarium cobalt iron and a 1:5 samarium copper cellular structure is formed, thereby preparing a material with excellent mechanical properties.

[0005] (ii) High-toughness fillers, such as copper-based nanowires, carbon nanotubes, etc., are mixed into conventional samarium cobalt magnetic powder. For example, Chinese invention patent application CN114628098A discloses a samarium cobalt permanent magnet and a preparation method thereof, wherein the toughness and impact resistance of the samarium cobalt permanent magnet are greatly improved by adding 0.5-2% Cu. Another example is Chinese invention patent application CN114121396A, which discloses a high-toughness samarium cobalt sintered magnet material and a preparation method thereof, wherein the toughening of the magnet is achieved by adding a toughening agent of nano-TiN coated with nano-Zn powder at 0.05-0.2% of the magnet alloy powder.

[0006] In terms of processing cracking, the difference between the above two technologies is very small, but the cost of both dopants is relatively high. Because, scheme (I) uses aging to control the mixing of two proportions of samarium cobalt magnets, but the process route is relatively long and not convenient for mass production. Scheme (II) has extremely high requirements for the added nanomaterials, and a large amount of high-quality and high-purity carbon nanotubes must be added and applied, otherwise the ideal toughening effect cannot be achieved. For example, after CN114628098A adds copper Cu, the magnetic properties are reduced by more than 20% compared to the maximum magnetic energy product of samarium cobalt magnets without copper; for example, after CN114121396A adds nano-TiN, the maximum magnetic energy product is reduced by 10%, and the magnet toughening effect is relatively general.

[0007] Therefore, the two existing methods for modifying high-toughness samarium cobalt magnets have the disadvantage of high cost, and the two processes also reduce other physical and chemical properties of samarium cobalt magnets to varying degrees, affecting the comprehensive application effect of samarium cobalt magnets. Therefore, there is still a lot of room for improvement in the mechanical properties of samarium cobalt magnets, and how to reduce magnet cracking during processing is still an urgent problem to be solved. Summary of the invention

[0008] The purpose of the present invention is to provide a high-toughness samarium cobalt magnet and a preparation method thereof, in view of the problems that samarium cobalt magnets in the prior art are prone to cracking and the existing toughening technology has high costs and poor effects. The invention can reduce the cracking of the magnet and ensure the qualified rate of the product; and can ensure the excellent mechanical properties of the magnet while also making the magnet have better magnetic properties.

[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0010] A samarium cobalt magnet, which is made of samarium cobalt magnetic powder and micron-grade copper calcium titanate;

[0011] in,

[0012] The particle size of samarium cobalt magnetic powder is 4-15μm;

[0013] The amount of micron-grade copper calcium titanate is 0.1wt%-1.5wt% of the samarium cobalt magnetic powder.

[0014] Note: wt% means weight percentage.

[0015] The samarium cobalt magnet of the present invention is a high-toughness samarium cobalt magnet with excellent crack resistance performance, which meets the processing performance requirements of more scenarios. The toughness of the samarium cobalt matrix material is improved by an appropriate amount of micron-grade copper calcium titanate (CCTO). Although the amount of CCTO is extremely low, it can greatly enhance the toughness. Due to the low amount of CCTO, on the one hand, the cost of processing samarium cobalt magnets is low, and on the other hand, the magnetic properties of samarium cobalt magnets are closer to the magnet products processed and formed by pure samarium cobalt magnetic powder. Compared with the aging method or carbon nanomaterial doping process of the prior art, the cost of adding and applying CCTO in the method of the present invention is only a fraction of that of carbon nanomaterials, and the toughness improvement effect on the samarium cobalt matrix material is better. And the magnetic properties of the samarium cobalt magnet are basically the same as those of ordinary samarium cobalt magnets, which does not affect the normal application of the magnet. Among them, the particle size of the samarium cobalt magnetic powder refers to the average particle size.

[0016] Furthermore, the fracture strength of the samarium cobalt magnet is above 768 MPa. The fracture strength is used to represent the toughness of the samarium cobalt magnet.

[0017] Preferably, the breaking strength of the samarium cobalt magnet is 768-900.

[0018] More preferably, the fracture strength is 780-880 MPa, such as 790 MPa, 800 MPa, 810 MPa, 830 MPa, 845 MPa, 855 MPa. For example, the fracture strength of samarium cobalt magnets reaches 843 MPa.

[0019] Furthermore, the roughcast cracking rate of the samarium cobalt magnet during processing is a, and a≤3.5%.

[0020] Preferably, a≤3.5%. Preferably, a≤3.3%. Preferably, a≤3.0%.

[0021] Preferably, a≤2.8%. Preferably, a≤2.54%. Preferably, a≤2.3%.

[0022] Furthermore, the remanence of the samarium cobalt magnet is Br, and Br≥10.7 kGs.

[0023] Preferably, Br≥11.0 kGs. Preferably, Br≥11.01 kGs.

[0024] Furthermore, the intrinsic coercive force of the samarium cobalt magnet is Hcj, and Hcj≥27kOe.

[0025] Preferably, Hcj≥27.5kOe. Preferably, Hcj≥28kOe.

[0026] Furthermore, the magnetic energy product of the samarium cobalt magnet is (BH) max , (BH) max ≥28MGOe.

[0027] Preferably, BH max ≥29MGOe. Preferably, BH max ≥29.5MGOe.

[0028] Furthermore, the samarium cobalt magnetic powder is 2:17 samarium cobalt magnetic powder and / or 1:5 samarium cobalt magnetic powder.

[0029] Preferably, 2:17 samarium-cobalt magnetic powder is used, the amount of rare earth element samarium used is small, the cost is low, and the overall performance of the magnet is good.

[0030] Furthermore, the particle size of the samarium cobalt magnetic powder is 4-12 μm. Preferably, the particle size of the samarium cobalt magnetic powder is 5-10 μm.

[0031] Preferably, the particle size D of the samarium cobalt magnetic powder is 50 =5.0-10.0 microns.

[0032] Preferably, the particle size D of the samarium cobalt magnetic powder is 90 =15.0-25.0 microns.

[0033] Furthermore, the samarium cobalt magnet is made of samarium cobalt magnetic powder and micron-grade copper calcium titanate. Preferably, it is formed by pressing.

[0034] Preferably, the samarium cobalt magnet is formed by hot-pressing and sintering samarium cobalt magnetic powder and micron-grade copper calcium titanate.

[0035] Furthermore, the particle size of the micron-sized copper calcium titanate is 1-5 microns.

[0036] Furthermore, the amount of the micron-sized copper calcium titanate is 0.2wt%-1.2wt% of the samarium cobalt magnetic powder.

[0037] Preferably, the amount of the micron-sized copper calcium titanate is 0.3wt%-1.0wt% of the samarium cobalt magnetic powder.

[0038] Preferably, the amount of micron-sized copper calcium titanate is 0.3wt%-0.9wt% of the samarium cobalt magnetic powder. For example, the amount of micron-sized copper calcium titanate can be 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, or 0.8wt%.

[0039] In order to ensure the acquisition of the above-mentioned high-toughness samarium cobalt magnet, the present invention also provides a preparation process method. By using the corresponding process method to process and prepare the magnet, the toughening effect of doped CCTO can be fully utilized to ensure that the magnetic properties of the samarium cobalt magnet are better.

[0040] A method for preparing the above-mentioned samarium cobalt magnet comprises the following steps:

[0041] S1. Take samarium cobalt magnetic powder with a particle size of 4-15 μm, mix micron-grade copper calcium titanate (CCTO) with the samarium cobalt magnetic powder to obtain mixed magnetic powder.

[0042] S2. The mixed magnetic powder is oriented and pressed by a rare earth permanent magnet forming press to obtain a green body, and then the green body is cold isostatically pressed to obtain a green body.

[0043] S3, sintering the green blank at 1160-1220°C to obtain a blank; after sintering, subjecting the blank to aging treatment to obtain a samarium cobalt magnet.

[0044] The samarium cobalt magnet, that is, a samarium cobalt magnet blank with high toughness, can be used for fine processing and is not easy to break.

[0045] The preparation method of the present invention obtains a samarium cobalt magnet with high mechanical properties and magnetic properties, wherein the added calcium copper titanate (CCTO) is a ceramic material that can help to evenly disperse the main components in the matrix, reduce phase interface defects, and improve the density and uniformity of the material. In addition, under high temperature conditions, CCTO can inhibit phase change and oxidation, thereby maintaining the magnetic properties and structural integrity of the material, thereby enhancing the high temperature performance of the samarium cobalt magnet and further improving the applicability of the samarium cobalt magnet for use in high temperature environments.

[0046] By adjusting the ratio of CCTO to magnetic powder, mixed magnetic powder with different CCTO contents was prepared. Experiments showed that when 0.1wt% to 1.3% CCTO was added, the magnetic property loss of the SmCo magnet blank was minimal, and the toughness of the magnet was significantly enhanced. The green blank was obtained by cold isostatic pressing of the green blank, which was denser than the green blank.

[0047] Further, in S1, the samarium cobalt magnet alloy ingot is prepared into samarium cobalt magnetic powder with a particle size of 4-15 μm, and micron-grade copper calcium titanate is mixed with the samarium cobalt magnetic powder to obtain mixed magnetic powder.

[0048] Further, in S1, the samarium cobalt magnetic powder is a powder with a particle size of 5-15 μm. Preferably, the samarium cobalt magnetic powder is a powder with a particle size of 5-10 μm.

[0049] Preferably, the samarium cobalt magnetic powder is prepared by casting a samarium cobalt magnet alloy ingot into magnetic powder with a particle size of 5-15 μm.

[0050] Further, in S1, micron-sized calcium copper titanate (CCTO) and samarium cobalt magnetic powder are mixed by a three-dimensional mixer. The three-dimensional mixer is used to fully mix the materials to ensure uniformity of the materials.

[0051] The micron-sized copper calcium titanate and samarium cobalt magnetic powder are fully mixed by a three-dimensional mixer.

[0052] Further, in S1, the samarium cobalt magnetic powder is 2:17 samarium cobalt magnetic powder and / or 1:5 samarium cobalt magnetic powder. 2:17 samarium cobalt magnet is also called Sm2Co17. It is a magnetic material mainly made of metal samarium and cobalt through smelting, crushing, pressing, sintering and aging. The maximum magnetic energy product is between 20-35 and the maximum operating temperature is 350°C. It has a low temperature coefficient and good corrosion resistance. It has outstanding magnetic properties at high temperatures and is widely used in aerospace, high-temperature motors, automotive sensors and microwave devices. 2:17 samarium cobalt is extremely brittle and not easy to be processed into complex shapes, such as thin sheets, thin-walled rings, etc. 2:17 and 1:5 are the current mainstream proportions of samarium cobalt magnets, with good magnetic properties and mature alloy production and processing technology. After the raw materials are smelted and cooled, the alloy is cast into ingots, which are then crushed to obtain micron-sized powder raw materials for blank pressing.

[0053] The existing samarium-cobalt alloy production line can be used to obtain the corresponding samarium-cobalt alloy ingots, which are then crushed and processed into powder to obtain samarium-cobalt magnetic powder.

[0054] Even, the SmCo alloy ingot for preparing the SmCo magnetic powder is a 2:17 and / or 1:5 SmCo alloy ingot.

[0055] Furthermore, the particle size of the micron-sized copper calcium titanate is 1-5 microns.

[0056] Furthermore, the amount of the micron-sized copper calcium titanate is 0.1wt%-1.3wt% of the samarium cobalt magnetic powder.

[0057] Preferably, the amount of the micron-sized copper calcium titanate is 0.3wt%-1.0wt% of the samarium cobalt magnetic powder.

[0058] Preferably, the amount of micron-grade copper calcium titanate is 0.3wt%-0.9wt% of the samarium cobalt magnetic powder, for example, the amount may be 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, or 0.8wt%.

[0059] Further, in S3, the sintering temperature is preferably 1170-1210°C.

[0060] Furthermore, in S3, the conditions for aging treatment of the blank are: temperature 830-870°C, time: 4-12h.

[0061] Preferably, the temperature is 830-860° C. and the time is 4-10 hours.

[0062] Further, in S3, sintering is performed using a vertical sintering furnace.

[0063] In addition, in the process method of the present invention, after the samarium cobalt magnet is sintered, an aging treatment is performed, and the aging treatment is selected at 830-860°C for 4-10 hours, so that the reinforcing phase effect of CCTO can be maximized without affecting the magnetic properties of the samarium cobalt magnet. The reinforcing phase effect of CCTO improves the toughness of the samarium cobalt matrix, and can improve the overall mechanical properties by improving the interphase bonding and the bonding strength between the reinforcing phase and the matrix.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] 1. The samarium cobalt magnet of the present invention can reduce magnet cracking and ensure the product qualification rate; and can ensure the excellent mechanical properties of the magnet while also making the magnet have better magnetic properties. The advantage is that the high-toughness samarium cobalt magnet of the present invention can retain good magnetic properties while maintaining mechanical properties.

[0066] 2. The preparation method of the present invention obtains a samarium cobalt magnet with high mechanical properties and magnetic properties, wherein the added copper calcium titanate (CCTO) is a ceramic material that can help to evenly disperse the main components in the matrix, reduce phase interface defects, and improve the density and uniformity of the material. After testing, the bending strength and fracture toughness of the samarium cobalt magnet are also significantly improved, and the mechanical stability of the magnet is improved. Adding CCTO at a ratio of 0.1-1.5wt%, especially preferably adding 0.3-0.9wt% CCTO can ensure that the ceramic CCTO forms a continuous reinforcement at the phase interface without causing side effects, and achieves the best mechanical properties and magnetic properties of the samarium cobalt magnet material, and the magnetic properties are close to 99% of the magnetic properties of traditional samarium cobalt magnets. At the same time, the fracture strength is increased by 8-80MPa or even more, and the cracking rate of the blank processing can be reduced by more than 50%.

[0067] 3. The preparation method of the high-toughness samarium cobalt magnet of the present invention is to fully mix micron-sized samarium cobalt magnetic powder and micron-sized copper calcium titanate (CCTO), orient and press them through a rare earth permanent magnet forming press to obtain a green body, then cold isostatically press the green body, and finally sinter at 1160-1220°C, preferably sinter at 1170-1210°C, to obtain a samarium cobalt blank with high toughness. The obtained samarium cobalt magnet has good toughness and extremely low modification cost. Compared with the traditional aging process or carbon nanomaterial doping, it has lower cost and is easier to process and prepare. The cost of traditional carbon nanomaterials as dopants to enhance toughness is almost times that of CCTO, and CCTO can greatly improve the toughness of the samarium cobalt matrix material. DETAILED DESCRIPTION

[0068] The present invention is further described in detail below in conjunction with test examples and specific implementation methods. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention.

[0069] Examples 1-8

[0070] Preparation of high toughness samarium cobalt magnets:

[0071] The 2:17 SmCo alloy ingot was crushed into 8μm±2μm SmCo magnetic powder. 50 =1.178μm, D 90 =1.906μm) was added to the magnetic powder in a weight ratio of 0.1-1.5wt% (the specific addition ratio is shown in Table 1), and the mixed magnetic powder was prepared by a three-dimensional mixer (three-dimensional motion mixer SYH-5, Shenzhen Kejing Zhida Technology Co., Ltd.).

[0072] The above pure samarium cobalt magnetic powder and mixed magnetic powder were oriented and pressed by a rare earth permanent magnet forming press to obtain green bodies. The pressure of the press was 12MPa and the orientation magnetic field strength was 1.6T. Then, the green bodies were cold isostatically pressed to obtain a denser green body, and finally sintered at 1190℃ in a vertical sintering furnace. Then, the aging treatment was performed at a temperature of 850℃ for 6h to obtain a samarium cobalt blank with high toughness.

[0073] The sintered samarium cobalt magnet blanks were processed, and the magnetic properties of the obtained samarium cobalt magnets were tested: remanence, intrinsic coercive force, and maximum magnetic energy product. Then, each samarium cobalt magnet sample was tested for fracture strength and blank processing cracking rate. In the fracture strength test process, multiple samples were prepared and the average value was taken. The test results are shown in Table 1 below.

[0074] Table 1 SmCo magnet performance test results

[0075]

[0076]

[0077] Among them, Example 1 adopts a solution without adding CCTO, and uses pure samarium cobalt magnetic powder to prepare samarium cobalt magnets by hot pressing and sintering, which represents traditional samarium cobalt magnets and serves as a negative control example to facilitate comparison of the improvement in magnet performance.

[0078] It can be seen from the performance test results of the samarium cobalt magnets obtained by the above-mentioned Examples 1-8 that a good skeleton reinforcement effect can be achieved by adding a certain amount of CCTO. During the sintering process of the samarium cobalt magnet, CCTO plays a role similar to fine grain strengthening, which solves the defect that the samarium element structure in the samarium cobalt magnet is fragile and easy to crack. Because the melting point of samarium in the samarium cobalt magnet is relatively low, it is first melted to form an alloy liquid to bond the magnets. The CCTO used in the present invention is added at a ratio of 0.1%-1.5%, giving full play to the high strength and high toughness characteristics of CCTO, forming a continuous network structure of the samarium element in the samarium cobalt magnet, and achieving a ceramic reinforcement effect.

[0079] In particular, the proportion of CCTO addition can be controlled between 0.2-1.0wt%, so that the loss of magnetic properties of the samarium cobalt magnet after modification is small (lower non-magnetic material doping addition). If the proportion of CCTO addition is large, the problem of reduced matching effect of CCTO and samarium is likely to occur, because too much CCTO cannot fully infiltrate and disperse, and also leads to poor continuity of samarium molten alloy liquid, reduced mechanical properties of materials, and reduced magnetic properties. In addition, too much CCTO will also increase the difficulty of controlling the uniformity of material mixing, resulting in the material being difficult to mix evenly, prone to segregation or excessive local CCTO content, and ultimately causing the sintering consistency of the samarium cobalt magnet to deteriorate, and both mechanical properties and magnetic properties are reduced.

[0080] Example 9

[0081] The 2:17 alloy ingot was prepared into 9μm±1μm magnetic powder, and 0.2wt% of micron-grade copper calcium titanate (same as CCTO in Example 1) was fully mixed with the magnetic powder through a three-dimensional mixer to obtain mixed magnetic powder. The mixed magnetic powder was pressed by a rare earth permanent magnet forming press in a 2.0T magnetic field orientation and 15MPa to obtain a green body, and then the green body was cold-pressed at 300MPa isostatically to obtain a denser green body.

[0082] Finally, the green blank is sintered at 1200°C in a vertical sintering furnace to obtain a samarium-cobalt blank with high toughness. The samarium-cobalt blank is aged under the following conditions: temperature 860°C, time: 10 hours. Then, it is machined and formed. In the above process, the sintering, aging, product specifications, and processing equipment remain unchanged, which are the same as those in Example 1.

[0083] The magnetic properties of the samarium cobalt magnet prepared in this embodiment are as follows: remanence Br 11.12 kGs, intrinsic coercivity Hcj 28.21 kOe, maximum magnetic energy product (BH) max 30.21 MGOe, and the magnetic properties are basically equivalent to those of conventional samarium cobalt magnets not doped with CCTO, without showing any degradation.

[0084] Then, the fracture strength and blank processing cracking rate of each samarium cobalt magnet sample were tested. The results showed that the maximum fracture strength of the samarium cobalt magnet doped with 0.2% CCTO reached 796Mpa. When the batch of samarium cobalt magnets was processed, the blank processing cracking rate was 3.02%, which was reduced by more than 25% compared with the samarium cobalt magnets without CCTO doping.

[0085] Example 10

[0086] Preparation of high toughness samarium cobalt magnets:

[0087] The 2:17 alloy ingot was prepared into 8μm±2μm magnetic powder by air flow milling machine. Micron-grade calcium copper titanate (CCTO) was added to the magnetic powder at a weight ratio of 0.6wt%, and fully mixed by a three-dimensional mixer to prepare mixed magnetic powder.

[0088] The mixed magnetic powder is oriented and pressed by a rare earth permanent magnet forming press to obtain a green body, with a pressure of 15 MPa and a magnetic field intensity of 2 T. The green body is then cold-pressed at 310 MPa to obtain a denser green body.

[0089] Finally, after sintering at 1190°C, 850°C and aging treatment for 6h in a vertical sintering furnace, a samarium-cobalt blank with high toughness was obtained.

[0090] The obtained samarium-cobalt blanks are cut and shaped, and then put into storage after passing inspection.

[0091] The same test method as in the above-mentioned Examples 1-8 was used to test the samarium cobalt magnet, and the remanence Br was measured to be 11.04 kGs, the intrinsic coercive force Hcj was 28.20 kOe, and the maximum magnetic energy product (BH) max was 30.03 MGOe. The magnetic performance was basically equivalent to that of the conventional samarium cobalt magnet not doped with CCTO, and there was basically no performance degradation. It can be considered that the magnetic properties have not changed.

[0092] Then, each samarium cobalt magnet sample was tested for fracture strength and blank processing cracking rate. The results showed that the maximum fracture strength of the samarium cobalt magnet reached 823Mpa after doping with 0.6% CCTO, indicating that the fracture strength of the samarium cobalt magnet increased significantly, with an increase of more than 8%. This batch of samarium cobalt magnets was finely processed, and the blank processing cracking rate was 1.91%. The processing efficiency of samarium cobalt magnets was significantly improved, because the amount of material scrap caused by cracking was greatly reduced.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A samarium cobalt magnet, characterized in that: The samarium cobalt magnet is made of samarium cobalt magnetic powder and micron-grade copper calcium titanate; in, The particle size of samarium cobalt magnetic powder is 4-15μm; The amount of micron-grade copper calcium titanate is 0.1wt%-1.5wt% of the samarium cobalt magnetic powder.

2. The samarium cobalt magnet according to claim 1, characterized in that The breaking strength of the samarium cobalt magnet reaches above 768 MPa.

3. The samarium cobalt magnet according to claim 1, characterized in that The samarium cobalt magnetic powder is 2:17 samarium cobalt magnetic powder and / or 1:5 samarium cobalt magnetic powder.

4. The samarium cobalt magnet according to claim 1, characterized in that The particle size of the samarium cobalt magnetic powder is 5-10 μm.

5. The samarium cobalt magnet according to claim 1, characterized in that: The particle size of the micron-sized copper calcium titanate is 1-5 μm.

6. The samarium cobalt magnet according to claim 1, characterized in that The amount of micron-sized copper calcium titanate is 0.2wt%-1.3wt% of the samarium cobalt magnetic powder.

7. A method for preparing a samarium cobalt magnet, characterized in that: The following steps are involved: S1, taking samarium cobalt magnetic powder with a particle size of 4-15 μm, mixing micron-grade copper calcium titanate with samarium cobalt magnetic powder to obtain mixed magnetic powder; S2, orienting and pressing the mixed magnetic powder through a rare earth permanent magnet forming press to obtain a green body, and then cold isostatically pressing the green body to obtain a green body; S3, sintering the green blank at 1160-1220° C. to obtain a blank; After sintering, the blank is subjected to aging treatment to obtain a samarium cobalt magnet.

8. The method for preparing a samarium cobalt magnet according to claim 7, characterized in that: In S1, the samarium cobalt magnetic powder is 2:17 samarium cobalt magnetic powder and / or 1:5 samarium cobalt magnetic powder.

9. The method for preparing a samarium cobalt magnet according to claim 7, characterized in that: In S3, the conditions for aging treatment of the blank are: temperature 830-870°C, time: 4-12h.

10. The method for preparing a samarium cobalt magnet according to claim 7, characterized in that: In S3, the amount of micron-sized copper calcium titanate is 0.1wt%-1.3wt% of the samarium cobalt magnetic powder.

Citation Information

Patent Citations

  • High-toughness samarium-cobalt sintered magnet material and preparation method thereof

    CN114121396A

  • Samarium cobalt permanent magnet and preparation method thereof

    CN114628098A